Description of injury to the victim of motorcycle traffic accident - Rusman, Andri A; Aflah, Livaldi N; Kusuma, Andri A (ACTA Medical Health Sciences, 2022)
Road accidents are events that can lead to injury or death. The number of fatalities from traffic accidents is the eighth highest in the world. In Southeast Asia, up to 316,000 people die each year in road accidents. Motorcycles are the type of vehicle with the highest number of accidents compared to other types of vehicles. The increase in motorcycle purchases in Indonesia is associated with an increase in road accidents. Road accident injuries can occur on multiple parts of the body and can cause different types of injuries. The purpose of this study is to determine the description of the victims of motorcycle traffic accidents in Southeast Asia. This research is a descriptive study using literature study method by searching various literature that uses electronic databases such as Google Scholar, ResearchGate, PubMed, NCBI, WHO, Ministry of Health, ScienceDirect, and Springer to search related literature. Keywords used when searching for items are injuries, car accidents, motorcycles, and Southeast Asian descriptions. A total of seven articles were selected for analysis using synthetic matrices, and the results showed that working-age and male gender were most frequently involved in motorcycle road accidents. Extremities injuries are the most common site of injury and the majority of injuries obtained are soft tissue injuries. In order to add data on the most common types of injuries to motorcycle traffic accident victims in Indonesia, this study needs to be further conducted in Indonesia on the most common types of injuries to motorcycle traffic accident victims. DOI : 10.35990/amhs.v1n2.p97-104 REFERENCES World Health Organization. Global status report on road safety 2018: Summary. Geneva: WHO; 2018. ISBN: 9789241565684. World Health Organization. Road safety in the Southeast Asia Region 2015. New Delhi: WHO Regional Office for South-East Asia; 2016. Saukko P, Knight B. Knight’s Forensic Pathology. 3rd ed. London: Hodder Arnold; 2004. 626 p. DOI: https://doi.org/10.1201/b13642 Direktorat Jenderal Perhubungan Darat. Perhubungan Darat dalam Angka 2013; 2013. Mu’in Muhammad DSDS. Gambaran karakteristik dan penyebab kejadian kecelakaan lalu lintas pada kelompok pekerja pengendara sepeda motor. Jurnal Keperawatan dan Kesehatan Masyarakat Cendekia Utama. 2017;6:32–9. E-ISSN: 2598-4217. World Health Organization. Global status report on road safety 2015. 2015 [cited]. Available from: https://www.who.int/violence_injury_prevention/road_safety_status/2015/GSRRS2015_Summary_EN_final.pdf Riyadina W, Subik IP. Profil keparahan pada korban kecelakaan sepeda motor di Instalasi Gawat Darurat RSUP Fatmawati. [Skripsi]. Jakarta: Univ-Medicine; 2007. Singh R, Singh HK, Gupta SC, Kumar Y. Pattern, severity and circumstances of injuries sustained in road traffic accidents: A tertiary care hospital-based study. Indian J Community Med. 2014;39(1):30–4. DOI: 10.4103/0970-0218.126353 Badan Penelitian dan Pengembangan Kesehatan, Kemenkes RI. Riset Kesehatan Dasar (Riskesdas) 2018. 2018. Available from: http://www.depkes.go.id/resources/download/infoterkini/materi_rakorpop_2018/Hasil%20Riskesdas%202018.pdf Isnu Lucky Riandini, R. S. Gambaran luka korban kecelakaan lalu lintas yang dilakukan pemeriksaan di RSUP Dr. M. Djamil Padang. Jurnal Kesehatan Andalas. 2015;4(2):502–8. DOI: https://doi.org/10.25077/jka.v4i2.283 Tinggi Ilmu Kesehatan Kendal S, Malik Ibrahim M, Sakundarno Adi M. Gambaran distribusi kejadian kecelakaan lalu lintas pada pengendara sepeda motor. Jurnal Ilmiah STIKES Kendal. 2018;8. DOI: https://doi.org/10.32583/pskm.8.2.2018.82-91 Undang-Undang Republik Indonesia No. 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan. 2009;12–42. Peraturan Pemerintah Republik Indonesia Nomor 43 Tahun 1993 Tentang Prasarana dan Lalu Lintas Jalan. 1993. p. 78. Utomo N. Analisa faktor penyebab kecelakaan lalu lintas pada segmen jalan By-Pass Krian-Balongbendo (Km.26+000–Km.44+520). Jurnal Teknik Sipil KERN. 2012;2(2):73–84. ISSN: 2087-7498. Buntara A. Cedera akibat kecelakaan lalu lintas di Indonesia: Faktor risiko serta strategi pencegahan dan intervensi. Jurnal Ilmiah Kesehatan Masyarakat. 2019;11:262–8. e-ISSN: 2684-9501. Marsaid, Hidayat M, Ahsan. Faktor yang berhubungan dengan kejadian kecelakaan lalu lintas pada pengendara sepeda motor di wilayah Polres Kabupaten Malang. Jurnal Ilmu Keperawatan. 2013;1(2):98–112. Krug EG, Sharma GK, Lozano R. Risk factors for road traffic injuries. Am J Public Health. 2000;90:523–6. DOI: 10.2105/ajph.90.4.523 Komite Nasional Keselamatan Transportasi. Studi tingkat kecelakaan lalu lintas jalan di Indonesia berdasarkan data KNKT dari tahun 2007–2016. Injury. 2017;43(1):6–7. DOI: http://dx.doi.org/10.25104/warlit.v29i2.557 Kresnowati L, Nuryati. Klasifikasi dan kodefikasi penyakit dan masalah terkait III. Kementerian Kesehatan Republik Indonesia; 2018. p. 283–313. CDC, NCIPC. Traumatic Brain Injury in News and Social Media. 2016 [cited Jul 8]. Available from: https://www.cdc.gov/traumaticbraininjury/pdf/guide-to-writing-about-tbi-in-news-and-social-media-a.pdf Galgano M, Toshkezi G, Qiu X, Russell T, Chin L, Zhao L-R. Traumatic brain injury. Cell Transplant. 2017;26(7):1118–30. DOI: 10.1177/0963689717714102 Gwinnutt CL, Driscoll P. Advanced trauma life support. Anaesthesia. 2018;48:441–2. DOI: 10.1111/j.1365-2044.1993.tb07026.x Najem D, Rennie K, Ribecco-Lutkiewicz M, Ly D, Haukenfrers J, Liu Q, et al. Traumatic brain injury: Classification, models, and markers. Biochem Cell Biol. 2018;96(4):391–406. DOI: 10.1139/bcb-2016-0162 Ng SY, Lee AYW. Traumatic brain injuries: Pathophysiology and potential therapeutic targets. Front Cell Neurosci. 2019;13(November):1–23. DOI: https://doi.org/10.3389/fncel.2019.00522 Alao T, Waseem M. Neck trauma [Internet]. StatPearls Publishing; 2021 [cited 2021 Jul 7]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK470422/ Muhammad MT, Waseem M. Cervical injury [Internet]. StatPearls Publishing; 2021 [cited 2021 Jul 20]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK448146/ Zeng J, Gong Q, Liu H, Rong X, Ding C. Complete fracture-dislocation of the thoracolumbar spine without neurological deficit. Medicine (Baltimore). 2018;97(9):e10050. DOI: 10.1097/MD.0000000000010050 Edgecombe L, Sigmon D, Galuska MA, Angus DL. Thoracic trauma [Internet]. StatPearls Publishing; 2021 [cited]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK534843/ O’Rourke M, Landis R, Burnsbracken. Blunt abdominal trauma [Internet]. StatPearls Publishing; 2021 [cited Jul 8]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK431087/ Ahmed M. Frequency and pattern of intra-abdominal injuries in patients with blunt abdominal trauma. J Trauma Treat. 2014;3(3):3–5. Abraham MK. Pelvic trauma. In: The Emergency Medicine Trauma Handbook. 2019. p. 260–72. DOI: 10.4172/2167-1222.1000196 Coccolini F, Stahel PF, Montori G, Biffl W, Horer TM, Catena F, et al. Pelvic trauma: WSES classification and guidelines. World J Emerg Surg. 2017;12(1):1–18. DOI: https://doi.org/10.1186/s13017-017-0117-6 Ramadhani RP, Romadhona N, Djojosugito MA, Hadiati DE, Rukanta D. Hubungan jenis kecelakaan dengan tipe fraktur pada fraktur tulang panjang ekstremitas bawah. J Integr Kesehatan Sains. 2019;1(1):32–5. DOI: https://doi.org/10.29313/jiks.v1i1.4317 Sop JL, Aaron. Open fracture management [Internet]. StatPearls Publishing; 2020 [cited 2021 Jul 25]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK448083/ Kitamura Y, Hayashi M, Yagi E. Traffic problems in Southeast Asia featuring the case of Cambodia’s traffic accidents involving motorcycles. IATSS Res. 2018;42:163–70. Badan Pusat Statistik (BPS). Perkembangan jumlah kendaraan bermotor menurut jenis (unit), 2017–2019. [cited 2021 Jul 30]. Available from: https://www.bps.go.id/indicator/17/57/1/jumlah-kendaraan-bermotor.html Schmitt K-U, Niederer PF, Cronin DS, Morrison B III, Muser MH, Walz F. Trauma Biomechanics. Springer International Publishing; 2019. p. 193–213. Hansen JT. Netter’s Clinical Anatomy. 4th ed. 2019. Asosiasi Industri Sepeda Motor Indonesia (AISI). Statistik distribusi penjualan unit sepeda motor. [cited 2021 Sep 21]. Available from: https://www.aisi.or.id/statistic/ Kaur Autar Singh, S., Syakti Nasution, I., Hayati, L., & Muh Ali. (2018). Angka kejadian korban kecelakaan lalu lintas berdasarkan hasil pemeriksaan luar Visum Et Repertum di RSUP Dr. Mohammad Hoesin Palembang. Biomedical Journal of Indonesia, 12(1), 3. Kementerian Kesehatan Republik Indonesia. (2019). Profil Kesehatan Indonesia 2019 (p. 5). ISBN 978-602-416-977-0. Consunji, R. J., Larona, A. L. J., Jumangit, A. C., & Ameratunga, S. N. (2013). Poster presented at the 9th World Conference on Injury Prevention and Safety Promotion. Injury Prevention, 47(3). Ramli, R., Oxley, J., Noor, F. M., Abdullah, N. K., Mahmood, M. S., Tajuddin, A. K., & McClure, R. (2014). Fatal injuries among motorcyclists in Klang Valley, Malaysia. Journal of Forensic and Legal Medicine, 26, 39–45. https://doi.org/10.1016/j.jflm.2014.06.007 Oktavianti, P. H. (2016). Prevalensi dan gambaran pola luka korban kecelakaan sepeda motor di Instalasi Forensik RSUP Sanglah Denpasar tahun 2013. Jurnal Ilmu Kedokteran, 7(1), 33. http://isainsmedis.id/ojs/ Cheong, H. S., Tham, K. Y., & Chiu, L. Q. (2021). Injury patterns in elderly cyclists and motorcyclists presenting to a tertiary trauma centre in Singapore. Singapore Medical Journal, 62(9), 482–485. https://doi.org/10.11622/smedj.20200384 Tan Chor Lip, H., Tan, J. H., Mohamad, Y., Ariffin, A. C., Imran, R., & Azmah Tuan Mat, T. N. (2019). Clinical characteristics of 1653 injured motorcyclists and factors that predict mortality from motorcycle crashes in Malaysia. Chinese Journal of Traumatology – English Edition, 22(2), 69–74. https://doi.org/10.1016/j.cjtee.2018.11.001 Anni Tiurma Mariana, F. S. T. D. (2018). Cedera akibat kecelakaan lalu lintas di Sleman: Data HDSS 2015 dan 2016. BKM Journal of Community Medicine and Public Health, 34, 230–235.